The Influence Promotion on Consumer Tastes In The Decision of Tourist to Visit Bangka Botanical Garden - Darwati Susilastuti; Pudji Astuty; Ernawan Rebuin (Return : Study of Management, Economic and Bussines, 2023)
Bangka Belitung Islands Province is the largest tin producer in Indonesia, which has an impact on mining activities with a poor pattern causing a number of damages. The presence of the Bangka Botanical Garden has provided a new breakthrough to repair the environment damaged by mining. This study aims to determine to determine the influence campaign that encourages travelers to visit Bangka Botanical Garden, to determine the effect of consumer tastes to encourage tourists to visit the Bangka Botanical Garden, and to determine the effect of promotion and consumer tastes in simultan which encourages tourists to visit the Bangka Botanical Garden in City Pangkalpinang Bangka Belitung Islands Province. The method used in this study a correlation method that aims to see how far the relationship between the campaign against the decision visiting of Botanical Garden Botanical Garden of tourists. From these results of obtained rs of 0.761. On a scale of Guilford is that there is a high relationship between the promotion of Bangka Botanical Garden with the decision of tourists visiting the Bangka Botanical Garden in City Pangkalpinang Bangka Belitung Islands Province. In this case, Ha accepted and Ho rejected. This means that tourism has been an effective media campaign and managed to increase the number of tourists visit to Bangka Botanical Garden in City Pangkalpinang Bangka Belitung Islands Province.